Testing for consumer preferences of smoked asian sea bass (Barramundi) filet products in Hungary - István Szűcs; Ildikó Edit Tikász; Milán Fehér; László Stündl; Len Tiu Wright (Cogent Business & Management, 2018)
The present paper discusses the findings of primary research related to the development of smoked fish filet made of the barramundi into a functional food, including product tasting. The study sought to provide information for the target audience, in our case, for consumers in hypermarkets on (1) about their certain fish consumption habits, (2) their attitudes towards conscious fish consumption, (3) the reputation of the barramundi brought to the domestic market recently and the related considerations of consumers and (4) consumers' perceptions of the latest product development, smoked barramundi enriched with substances of positive nutritional benefits (e.g. vitamin complex, pumpkin seed oil, Gingko Biloba extract, Sylibum marianum oil, etc.). On the basis of the research, it can be concluded that product development is on the right track, it fulfils all the habits, expectations and demands of the target audience for fish consumption.
Keywords: 650